2020
DOI: 10.1093/asjof/ojaa031
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection for Pedal Soft Tissue Augmentation

Abstract: Background Pedal fat grafting has been shown to improve pain and functional impairment from forefoot fat pad atrophy. Objectives We aimed to determine if patient demographics and foot characteristics play a role in the level of impact that is achieved following surgery. Methods We performed a retrospective review of patients who received forefoot autologous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…14 PFG has been successfully implemented as treatment for a number of pedal conditions such as diabetic foot ulcers, pedal fat pad atrophy, thromboangiitis obliterans, plantar fibromatosis, and plantar osteochondromas. 4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Although it has be shown that grafted lipoaspirate redistributes over time in the plantar foot surface, it retains its supportive and analgesic function. 22 Considering this, the investigators expected that PFG holds potential therapeutic benefit to treat conditions, which results in elevated localized pedal pressure by providing a mechanism to dissipate said elevated pressure.…”
Section: Introductionmentioning
confidence: 99%
“…14 PFG has been successfully implemented as treatment for a number of pedal conditions such as diabetic foot ulcers, pedal fat pad atrophy, thromboangiitis obliterans, plantar fibromatosis, and plantar osteochondromas. 4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Although it has be shown that grafted lipoaspirate redistributes over time in the plantar foot surface, it retains its supportive and analgesic function. 22 Considering this, the investigators expected that PFG holds potential therapeutic benefit to treat conditions, which results in elevated localized pedal pressure by providing a mechanism to dissipate said elevated pressure.…”
Section: Introductionmentioning
confidence: 99%
“…However, external devices are prone to breakdown, and are inconvenient and cause patient compliance issues. In recent years, studies have demonstrated that pedal fat grafting significantly increases metatarsal fat pad volume and is beneficial for the treatment of pedal fat pad atrophy 8,9 . However, there is only 1 report of a pilot study of fat transplantation to treat chronic heel pain in adults after surgery for flat foot deformity 10 .…”
mentioning
confidence: 99%
“…In recent years, studies have demonstrated that pedal fat grafting significantly increases metatarsal fat pad volume and is beneficial for the treatment of pedal fat pad atrophy. 8,9 However, there is only 1 report of a pilot study of fat transplantation to treat chronic heel pain in adults after surgery for flat foot deformity. 10 In addition, traditional fat transplantation has a high absorption rate.…”
mentioning
confidence: 99%